2009
DOI: 10.1007/s12552-009-9002-6
|View full text |Cite
|
Sign up to set email alerts
|

From Separate Corners to Dialogue and Action

Abstract: How can higher education programs engage students in building a shared commons to address inequalities and foster commitment to intergroup collaboration? Intergroup dialogue is one such possibility to provide forums for meaningful engagement among students from diverse backgrounds. Findings from field experiments at nine colleges and universities show that students in intergroup dialogues increased significantly more than counterparts in control groups and social science comparison groups in their critiques of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…A Multi-University Intergroup Dialogue Research Project implemented random-assignment field experiments at nine higher education institutions to evaluate the efficacy of intergroup dialogues focused on race or gender (Nagda, Gurin, Sorensen, Gurin-Sands, & Osuna, 2009). The study found that students who participated in intergroup dialogues that were focused on race were better able to critique inequality, when compared to their counterparts in control and comparison groups.…”
Section: Intergroup Dialoguementioning
confidence: 99%
“…A Multi-University Intergroup Dialogue Research Project implemented random-assignment field experiments at nine higher education institutions to evaluate the efficacy of intergroup dialogues focused on race or gender (Nagda, Gurin, Sorensen, Gurin-Sands, & Osuna, 2009). The study found that students who participated in intergroup dialogues that were focused on race were better able to critique inequality, when compared to their counterparts in control and comparison groups.…”
Section: Intergroup Dialoguementioning
confidence: 99%
“…In contrast to these studies, a national study of intergroup dialogue (IGD) found that participants expressed greater intent to be involved in social justice actions than did comparison groups with no IGD (Nagda, Gurin, Sorenson, Gurin-Sands, & Osuna, 2009). IGD's success in motivating participants to take social action was likely due to its intentional learning design.…”
Section: Intergroup Contact Theorymentioning
confidence: 94%
“…For years, leaming theorists have suggested that the most effective learning models are those that include cognitions, concrete experiences, and reflection (Kolb, 1984;Nagda et al, 2009), such as are provided by this type of dialogue. Bain (2004) suggested that we have constructed mental models throughout our life and that they are slow to change even in the face of overwhelming proof.…”
Section: Intergroup Contact Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…All students who expressed a desire to be enrolled in the race/ethnicity dialogue completed an application. As each campus representative received applications they were randomly assigned into one of two groups: an experimental group and a wait-list control group (Nagda, Gurin, Sorensen, & Zúñiga, 2009;Nagda, Sorensen, Gurin-Sands, & Osuna, 2009). The experimental group was comprised of students who were then enrolled in the race/ethnicity dialogues, and the control group consisted of students placed on a waitlist that offered enrollment in a dialogue the following semester.…”
Section: Design Of the Study Experimental Design With Stratified Randmentioning
confidence: 99%